Preventable admissions and emergency-department-visits in pediatric asylum-seeking and non-asylum-seeking patients - Brandenberger, Julia; Bozorgmehr, Kayvan; Vogt, Florian; Tylleskär, Thorkild; Ritz, Nicole (International journal for equity in health, 2020)
Migrant health has become an essential part of public health. According to the World Health Organization, many health systems in Europe have not yet adapted adequately to the needs of asylum-seekers, which might result in untimely and inefficient health care for asylum-seeking patients. The aim of this study was to assess the number of preventable hospital admissions and emergency department visits in asylum-seeking and non-asylum-seeking pediatric patients.
Gesehen am 16.06.2020